Manajemen Kurikulum Projek Penguatan Profil Pelajar Pancasila untuk Mewujudkan Imtaq pada Siswa di SDN Warungdowo I Pasuruan - Khusnul Khotimah; Wahidmurni; Parmujianto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Along with the change from the 2013 curriculum to an independent curriculum at the start of the 2022/2023 academic year. SDN Warungdowo I is one of the basic education institutions in Pasuruan Regency that was selected by the Ministry of Education and Culture to take part in the Class 2 Mobilization School Program. For this reason, researchers chose this institution to be the place for research on the Project for Strengthening the Profile of Pancasila Students (P5). The aim of this research is to reveal the design, implementation and results of the implementation of the Pancasila Student Profile Strengthening Project curriculum to realize imtaq for students at SDN Warungdowo I Pasuruan. Case study research method, because it can describe contemporary empirical research in a real life context. The research results show that the design of the P5 curriculum goes through a module planning process, organizing it using a block system at the end of the semester, and the P5 theme of the institution is a sustainable lifestyle with an evaluation system using assessment rubrics, and student performance. Implement P5 by carrying out activities according to the P5 module for each phase, using an assessment rubric with a checklist system, the P5 process goes through the stages of orientation, contextualization, action and reflection. Based on the recap of the assessment rubric, the results of its implementation in the Imtaq dimension with elements of morals towards nature reached 53%, the mutual cooperation dimension 27%, and the creative dimension 31%. Thus, it can be concluded that curriculum design and implementation of P5 play an important role in realizing the Imtaq dimension in students.